Group Guidance with Alternative Interpretation Techniques to Enhance Social Self-Acceptance in Vocational Students - Hajar, Siti; Siregar, Alfin (Yayasan Sembilan Pemuda Indonesia, 2025)
This quasi-experimental study evaluated the effectiveness of group guidance with alternative interpretation techniques to enhance social self-acceptance in 16 vocational students (Vocational High School PAB 12 SAENTIS, Indonesia). Using a pretest-posttest control design, social self-acceptance was measured via a Likert-scale questionnaire based on Sheerer’s (2010) framework. Results showed significant improvement in the experimental group (pretest M = 68.75, posttest M = 127, p < 0.001), with normality (Shapiro-Wilk p > 0.05) and homogeneity (Levene’s p = 0.564) confirmed. Qualitative findings highlighted increased self-confidence and peer support. The study demonstrates that alternative interpretation techniques effectively improve social self-acceptance, addressing a gap in non-Western educational settings. Despite its promising results, the study is limited by a small sample size, short intervention duration, and lack of long-term follow-up. Future research should involve larger and more diverse populations and explore sustained behavioral outcomes over time. The findings have practical implications for integrating structured cognitive techniques into school counseling programs to support students’ psychosocial development.